Pengembangan Teknologi ERP Modul Customer Relationship Management Studi Kasus Rumah Makan Nasi Uduk “BABE” - Nurul Wahidah; Eka Prasetyaningrum; Lukman Bachtiar (Journal of Computer System and Informatics (JoSYC), 2020)
The implementation of Enterprise Resource Planning (ERP) as one of the supports for the operation of an integrated business sector and better data accuracy. An ERP system consists of various modules and sub-modules that can represent certain business components, one of which is CRM. Application of Customer Relationship Management (CRM) or customer relationship management which is indirectly said to be computerizing customer data. This is intended so that the company knows what the needs and desires of customers are so that good relationships can be established with customers. In East Kotawaringin, there is now a place to eat called Rumah Makan Nasi Uduk "Babe". This restaurant is a small business engaged in the sale of food. This restaurant serves direct customer orders, namely coming to the restaurant and by telephone. This ordering process goes through a very long route, where the prospective customer will choose the food menu and the restaurant records the menu ordered by the customer to the notebook and calculates how much the customer has to pay, then the customer waits for confirmation of the specified price. In connection with the aforementioned problems, a web-based application design is proposed so that in the future it can provide services about detailed information on food menus, prices and orders to customers. The research method used in this report is divided into several stages, namely the data collection stage, the system design stage, the program development stage, the program trial stage and the implementation stage. The conclusion of this research is that an ERP system has been successfully developed for a web-based CRM module with a case study of the "Babe" Nasi Uduk Restaurant.